Inclusion-body myositis: a difficult diagnosis? - Carolina da Cunha Correia; Maria Clara de Oliveira Magalhães; Pedro Lucas de Mendonça Barbosa; Eliene Dutra Campos; Edmar Zanoteli (Sociedade Brasileira de Patologia Clínica, 2014)
Sporadic inclusion-body myositis (IBM) is the most common myopathy in individuals over 55 years of age. However, in many cases, the diagnosis is neglected. Its main findings include progressive muscle weakness, normal or low levels of serum creatine kinase, and the absence of a response to immunosuppression. Muscle biopsy shows inflammatory reaction in association with degenerative changes of the muscle fibers. We report a typical case of IBM, in which diagnosis was possible only after three muscle biopsies. The challenges to confirm histological diagnosis and the caution to avoid repeating tests are discussed.